Phosphorus released by pigeonpea - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Pigeonpea can release and use soil phosphorus that is unavailable to other crops. Crops that follow pigeonpea benefit not only from residual nitrogen, but from extra phosphorus as well. Scientists at the International Crops Research Institute for...